Engineering constrained peptides to target nucleic acids: G-quadruplex recognition and imaging - Yavorova, Yaneva Militsa (Nanyang Technological University, 2022)
Recently, drug discovery has focused on developing targeted therapy methods, which requires identifying the exact cellular processes and molecular interactions. Peptides are highly functional molecules that can be tailored to achieve desirable properties which make them an attractive therapeutic agent. In this study, we applied and developed methods to engineer constrained peptides to recognise a special DNA structure, called G-quadruplex (G4). G-quadruplexes are four-stranded non-canonical nucleic acids secondary structures that are found in human genome and their formation and stabilization is linked to genome instability and cancer. Thus, these unique nucleic acids structures have become attractive targets for therapeutic design of molecules. In the past decades, several classes of compounds have been developed to stabilized and target G4s. However, despite the high number of known G4-targeting ligands, there is still a need for highly selective and specific one. Peptides are promising candidates to serve the role of specific G-quadruplex-targeting molecules. In this work, the two main approaches for constraining and stabilising peptides – stapling and cyclisation have been employed. Additionally, a novel method for synthesis of double constrained peptides has been developed. Our results showed that all engineered constrained peptides exhibit enhanced serum stability in comparison to their linear precursors, while the affinity to their biological target is retained or even improved in some cases. Finally, we have developed a peptide-fluorescent probe for specific G4-targeting in cells. In summary, we can conclude that peptides are among the most promising functional ligands for G-quadruplex targeting, allowing to control and visualize various biological processes.